The Chinese-American competition in the field of strong artificial intelligence (self-driving) - Amin, Sarmad Abdel Sattar; Oreibi, Zeina Malik (The International and Political Journal, 2022)
Strong artificial intelligence technology is witnessing a state of competition between a group of major countries, most notably China and the United States of America. The natural person represents a very developed type of smart systems that have been developed in recent years, so this research attempts to define self-leadership and its most important applications and how China and the United States have invested in it to develop their capabilities and to obtain as much power as possible to dominate the international system.